Indonesian Muslim Youth and The Korean Pop Wave (Case Study of Ponorogo Muslim Youth Students) - Murdianto, Murdianto; Zachari, A. `Ainun Zeva (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
Pop culture, a culture produced in a commercial ecosystem, is often interpreted as a light, contemporary, and fun culture so that it is easily accepted and enjoyed by the public, especially teenagers. Korean Pop Culture, for example, extends its influence throughout the world, not only in Indonesia. K-pop has attracted the sympathy of young people, including Muslim youth at Madrasah Aliyah Negeri (MAN) 2 Ponorogo. This study examines the perception of Muslim youth at Madrasah Aliyah Negeri 2 Ponorogo on Korean Pop Culture and its impact on Muslim youth at the school. This research uses a descriptive qualitative research method by purposively selecting research subjects, namely Muslim youth students of MAN 2 Ponorogo who love Korean pop culture. This study shows that, firstly, the Muslim youth of man 2 Ponorogo perceives Korean Pop Culture as a symbol of novelty, trending, unique, colorful, combining various elements. Secondly, the Muslim youth of MAN 2 Ponorogo realize Korean Pop Culture has a positive and negative impact, which can eliminate Korean Pop Culture products that are not relevant to their identity as millennial teenagers and Indonesian Muslims.